2016
DOI: 10.1093/eurpub/ckw070
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in breast cancer incidence and mortality in Europe—a systematic review and meta-analysis

Abstract: Background: Breast cancer is the leading cause of female cancer in Europe and is estimated to affect more than one in 10 women. Higher socioeconomic status has been linked to higher incidence but lower case fatality, while the impact on mortality is ambiguous. Methods: We performed a systematic literature review and meta-analysis on studies on association between socioeconomic status and breast cancer outcomes in Europe, with a focus on effects of confounding factors. Summary relative risks (SRRs) were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
3
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(190 citation statements)
references
References 38 publications
(207 reference statements)
10
169
3
8
Order By: Relevance
“…What is more important, revealed by the analysis, is that both low and high economic status could be associated with an elevated risk of breast cancer. Existing studies have suggested a positive association between high SES with the risk of breast cancer owing to the use of hormone therapy and lifestyle (Yu et al 2014;Palmer et al 2012;Akinyemiju et al 2015;Lundqvist et al 2016;Conroy et al 2017). Such association was also confirmed in this study.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…What is more important, revealed by the analysis, is that both low and high economic status could be associated with an elevated risk of breast cancer. Existing studies have suggested a positive association between high SES with the risk of breast cancer owing to the use of hormone therapy and lifestyle (Yu et al 2014;Palmer et al 2012;Akinyemiju et al 2015;Lundqvist et al 2016;Conroy et al 2017). Such association was also confirmed in this study.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Furthermore, the greater likelihood of alcoholic consumption in women with high SES may also lead to a high blood level of estrogen, which could contribute to the increase of breast cancer risk (EHBCCG 2011). More recently, Lundqvist et al (2016) conducted a systematic review and meta-analysis of studies on the association between breast cancer and SES in Europe. They found that women with higher SES tend to have significantly higher breast cancer incidence owing to factors such as hormone replacement therapy, mammography screening, reproduction, and lifestyle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The differences in stages at diagnosis are essentially due to disparities in health services availability, a highly prevalent situation in Latin America and other developing countries, but also already reported in the USA 15,16 , Europe 6,17 and other countries of the world. In fact, an analysis of GLOBOCAN statistics has been conducted, demonstrating that breast cancer-related mortality is directly associated with the Human Development Index 18 , with one of the reasons being late detection, aggravated by unavailability of best treatments.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to late diagnosis, other breast cancer epidemiological particularities have been reported in our country, such as presentation at earlier stages than in developed countries, which entails a higher impact on national public health services since it primarily affects women at productive age 5 . On the other hand, significant differences have been reported even within developed countries in both detection and treatment of breast cancer owing to sociodemographic and economic factors, with a direct impact on mortality 6,7 . In developing countries, the gaps in detection and quality of care are broader than in developed countries, and Mexico is not an exception.…”
Section: Introductionmentioning
confidence: 99%
“…Another critical limitation was the lack of individual socioeconomic information for more than two-thirds of the study population. Breast cancer incidence increases with socioeconomic status (possibly due to reproductive factors associated with socioeconomic status such as age at first birth and parity) (33), and increasing socioeconomic status often provides increasing resources to select residential areas less exposed to traffic noise. This makes socioeconomic status an important potential confounder, as well as a surrogate for socioeconomic-related risk factors.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%